2019
DOI: 10.1007/s41230-019-9013-x
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution of A380 aluminum alloy during rheological process under applied pressure

Abstract: S queeze casting can be supposed as a combination of casting and forging [1, 2]. In this process, high pressure is applied to the melt during solidification to obtain fine grains. The essence of mold-filling and feeding is rheological solidification of the alloy melt under pressure. Microstructure evolution is inevitable in this process, which affects the mold-filling and feeding in turn. Therefore, research on microstructure evolution during the rheological process under applied pressure is extremely meaningf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The rheological behaviour of the alloy has a crucial effect on the mould lling ability according to uid dynamics [12,13]. However, rheological behaviour and stopping the rheological mechanism of liquid-solid alloy melt are relatively complicated.…”
Section: Introductionmentioning
confidence: 99%
“…The rheological behaviour of the alloy has a crucial effect on the mould lling ability according to uid dynamics [12,13]. However, rheological behaviour and stopping the rheological mechanism of liquid-solid alloy melt are relatively complicated.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, increasing the pouring temperature is also benefit on the filling ability of alloy melt, but it should not be too high, otherwise it would easily cause the defects of entrainment in the rheological squeeze casting [13][14]. Many studies have also shown that chemical composition and fine-grained structure were beneficial to the filling ability of aluminum alloys [15][16][17]. However, the method of calculating filling ability and pressure loss of semi-solid rheological behavior in squeeze casting is still unclear and cannot provide guidance for squeeze casting of thin-walled parts.…”
Section: Introductionmentioning
confidence: 99%